The Play of Language in Ancient Greek Comedy (De Gruyter, 2024)
Within this volume, aspects of linguistic humour in ancient Greek comedy are explored. A rich repertoire of verbal artifices and types of joke is analysed, with emphasis on their contribution to the creation of comic effect and the aesthetic function of the plays. The examination ranges over the entire history of ancient Greek comic drama, from Aristophanes to New Comedy. A survey of recent research on the language of Greek comedy is included.